#Reúne, familias que buscan estrategia de incidencia en redes sociales sobre la problemática de las personas desaparecidas - Martos Castañeda, Alicia Dafne (2023)
The article explores the impact of the social media campaign ¨Reune, familias que buscan¨ that was launched in 2015 as a Facebook Fanpage that promoted the promulgation of a law to search for missing persons in Peru due to the consequences of the years of armed violence from 1980 to 2000 (Congreso de la República del Perú, 2016). Such a legal framework allows addressing in a comprehensive and humanitarian manner the search, identification and return of the more than 21,000 remains of missing persons to their respective families. "Reune, familias que buscan" was also born to raise public awareness of the need to search for missing persons, a pending issue years after the end of the internal armed conflict (Comisión de la Verdad y Reconciliación [CVR], s.f.). The paper proposes to analyze the differentiating element from other communication strategies in the human rights framework. The shift towards a humanitarian narrative, the use of a neutral, conciliatory, clear and transparent language, but mainly the articulation between diverse actors such as relatives of disappeared persons, authorities, civil organizations and State institutions contributed to avoid questioning from sectors adverse in the treatment to human rights issues and to join an initiative that used social networks as a window to express the needs of victimsof violence. Opinion leaders, actors, religious leaders, musicians and athletes participated in the initiative and joined to advocate for the need to promulgate the law on the search of missing persons. The advocacy achieved by "Reune, familias que buscan" is evidenced in the promulgation of the law on the search of missing persons (June 2016), and in a second stage, with the same strategy the Genetic Data Bank Law (September, 2018). (Presidencia de la República del Perú, 2018).